Fiqh Economic Analysis in the Implementation of Green Sukuk as a Form of SDGs - Helin Syafitri; Hulwati; Duhriah (Jurnal Ilmiah Ekonomi Islam, 2025)
This study discusses the application of green sukuk as an Islamic financial instrument in supporting the achievement of the Sustainable Development Goals (SDGs). Green sukuk is designed to fund environmentally friendly projects, such as renewable energy, waste management, and conservation of natural resources, while still adhering to the principles of economic fiqh, namely Justice (al-adl), balance (tawazun), and environmental preservation (hifdzul bi'ah). This study uses a qualitative approach with descriptive analytical methods to analyze the potential, challenges, and contribution of green sukuk to sustainable development. The results show that green sukuk has a positive impact on the environment, social, and economy, and contributes greatly to supporting the Sustainable Development Goals (SDGs) and has the potential to become an innovative Islamic financing solution. However, there are challenges in the form of low public understanding, lack of private sector participation, and the need for supportive regulation. Public education, government incentives, and the use of technology such as blockchain are important strategies to improve transparency and efficiency of fund management. This study recommends collaboration between the government, private sector, and academia to expand the implementation of green sukuk. With a comprehensive approach, green sukuk can strengthen Indonesia's position as a pioneer of Sharia green finance, while supporting sustainable development that is inclusive and environmentally friendly. Keywords: Green Sukuk, Fiqh Economics, SDGs